Ageism in the Workplace: A Review of the Literature - Bora Jin; Lisa Baumgartner (Adult Education Research Conference, 2019)
This literature review will examine literature concerning ageism in the workplace and the influence on older adults’ workplace learning. Findings have implications for employers, employees, and adult educators.
Keywords: ageism; workplace; older adult learning